Review on heat transfer augmentation in helically coiled tube heat exchanger - Md Atiqur Rahman (International Journal of Thermofluids, 2024)
In contemporary times, Helical tube heat exchangers (HTHXs) have gained significant prominence in energy-related sectors, frequently finding application in industrial and technical settings. Their impact on overall system efficiency and size is substantial. A comprehensive review addressing passive heat transfer enhancement methods in HTHXs is notably absent. This paper justifies its significance by providing a recent and systematic review of available passive methods. The passive approach offers advantages such as the absence of external power requirements and lower operational costs compared to active methods.This paper differentiates active and passive approaches. Studies collectively indicate a noteworthy progression in heat transfer enhancement in HTHXs. The paper meticulously evaluates passive methods like fins, inserts, geometry modifications, and baffles. Both experimental and numerical studies focus on improving heat transfer in HTHXs. However, further exploration is necessary to understand the negative effects of pressure drop in tube-side flow. Papers covering trends in future research should also prioritize the development of geometric designs for HTHX surfaces, potentially incorporating materials coatings to enhance heat transfer further. The authors present insightful issues and ideas that they estimate deserving of additional investigation in subsequent research endeavors